Reduction of ammonium and nitrate ions leaching in a tropical peat soil using clinoptilolite zeolite - Alicia Vanessa Jeffary. (Universiti Putra Malaysia, 2014)
One of the major problems in cultivating tropical peat soils is loss of plant nutrients such as nitrogen (N). Loss of N through leaching causes such as environment pollution and higher cost of fertilization in agriculture. The objective of this study was to determine the effectiveness of using clinoptilolite zeolite to reduce ammonium and nitrate ions leaching in tropical peat soils. Leaching experiment was carried out to compare the effectiveness of mixing urea with clinoptilolite zeolite and without clinoptilolite zeolite in minimizing ammonium and nitrate loss through leaching using standard procedures. The leaching experiment was carried out for 31 days and during this period, leachates were collected every 2 days and analyzed for NH4+, NO3-, and pH using standard procedures. At 31 days of leaching, soil samples were analyzed for total N, NH4+, NO3-, pH, and CEC using standard procedures. The treatment with clinoptilolite zeolite significantly reduced leaching of NH4+ and NO3- ions.This treatment also increased soil total N, NH4+, NO3-, CEC and pH at 31 days of leaching. These findings were possible because of the adsorption and absorption properties of clinoptilolite zeolite. Hence, clinoptilolite zeolite can be used to reduced ammonium and nitrate leaching in tropical peat soils but field experiment should be carried out to confirm these findings.